INPUT OF DOMESTIC WASTE IN THE ESTUARY OF DUMAI RIVER AND MESJID RIVER INTO THE RUPAT STRAIT WATERS - Dewi, Anggie Sukma; Nedi, Syahril; Amin, Bintal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
The study was conducted in December 2022 in the Dumai River Estuary and Dumai City Mesjid River Estuary, Riau Province. The purpose of this study is to determine the amount and type of garbage that enters the sea through the estuary of the Dumai River and the Mesjid River, the difference between the amount and type of waste, and the difference between days from the garbage contained in the estuary of the Dumai River and the Mesjid River in Dumai City. The research method used is a direct survey method in the field, where data collection is carried out directly at low tide using a net stretched at the mouth of the river so that garbage is collected and trapped following the river's flow into the net. Based on the research conducted, it was found that the types of waste trapped were plastic, foamy plastic, cloth, paper, rubber, and wood. The amount of input and composition of waste in two weeks to the mouth of the Dumai River was 28,26 kg in the first week and 30,64 kg in the second week, while in the estuary of the Mesjid River, it was less, namely the first week as much as 20,59 kg, and in the second week as much as 19,44 kg. The difference between the amount and type of waste contained in the Dumai River and the Mesjid River for two weeks found that plastic waste occupied the most significant amount, namely 30,43 kg with a composition of 51,55% and 49,71 kg with a composition of 49,71% based on total waste input. The difference in waste input based on the day at the mouth of the Dumai River and the highest Mesjid River is found on Sunday, namely at the mouth of the Dumai River with a total waste of 27,79 kg and at the mouth of the Mesjid River with a total of 16,67 kg.